Women in Bioorganic Chemistry - Cardona, Francesca; Parmeggiani, Camilla; Matassini, Camilla (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Issues relating to the gender schism and its effect on the career advancement of women in the Academy, especially in the field of STEM disciplines, deserve our attention and the efforts of all the scientific community to mitigate the gender gap. In order to embrace gender equality, recognize the career progression of women, and to celebrate the achievements of women in the field of bioorganic chemistry, we present contributions both from highly renowned female scientists and young female researchers who are in the early stages of their careers. This Special Issue includes fifteen manuscripts, including eleven high-quality research articles and four comprehensive review articles in the area of bioorganic chemistry, published from mid-2020 to early 2022. The scope of this Special Issue covers a wide range of topics at the organic chemistry-biology interface, including the synthesis and derivatization of natural compounds and their analogues, and the investigation of their biological activities in the human health field (for instance as antitumorals, antioxidants and antimicrobial agents), as well as their possible application in the crop protection field as agrochemicals. An example of nanoparticle-based biomaterial is also included. The techniques employed, besides organic synthesis, are in silico studies (docking procedures and molecular modeling), FT-IR spectroscopy, laser diffraction, PET, fluorescence, STD-NMR studies, enzymatic evaluation, experiments on cell lines and in vivo studies on mice.